Children's Knowledge Level about Oral Health Before and After Dental Health Education (DHE) through Educational Videos - Hanifan Aulia; Sri Ratna Laksmiastuti; Dhyani Widhianingsih (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: The Ministry of Health’s Basic Health Research (Riskesdas) in 2018 showed that the largest proportion of dental and oral problem is among the age group of 5-9 years (67.3%) where only 14.6% have received treatment by dental professionals. This is due to a lack of knowledge about maintaining oral health in children, and one of the health efforts to reduce dental and oral problems is to provide Dental Health Education (DHE). Generally, DHE activities are carried out face to face and practiced together in the field. The implementation during the Covid-19 pandemic requires a strategy that considers health and security aspects to prevent the transmission of the virus. Objectives: This research aims to determine the difference in children's knowledge level about dental and oral health before and after DHE with educational video media. Methods: This is an experimental analytic research with a cross-sectional study design. It was conducted at the Alamy Integrated Islamic Elementary School in Subang, where third-grade students completed the pre-test before watching the educational video, and post-test after watching video. Results: The average value of children's dental and oral health knowledge before and after being treated was 40.0 and 42.1, respectively. Furthermore, the Wilcoxon test showed a significant effect on the provision of DHE to children's knowledge about oral health. Conclusion: The provision of DHE significantly affects children's knowledge conveyed through educational videos.